Effect of Streptozotocin on Biochemical Parameters in Rats - Ragbetli, Cennet; Ceylan, Ebubekir (Asian Journal of Chemistry, 2010)
This study was carried out to investigate whether streptozotocin induced diabetic rats could effect some of serum biochemical parameters. Twenty Sprague-Dawley albino rats were divided into two experimental: Control (50 mg/kg SF) and streptozocin (60 mg/kg), Control rats were given only physiological saline (50 mg/kg). Serum glucose, AST, ALT and cholesterol levels of rats were determined after treatment of 1, 3 and 6 h, while the level of glucose, aspartate amino transferase (AST) and alanine amino transferase (ALT) were increased and cholesterol level was decreased. It is concluded from the experimental study that streptozocin (60 mg/ kg) may increase of serum glucose, AST, ALT levels and cause diabet in rats.